1982
DOI: 10.1002/aja.1001650308
|View full text |Cite
|
Sign up to set email alerts
|

The formation of the primitive choanae and the junction of the primary and secondary palates in the mouse

Abstract: This study has followed the development of the primary choanae in the mouse and has shown that they originate at the developmentally strategic position of junction between the primordia of the primary and secondary palates and that this basic anatomic relationship is maintained throughout further development. Involution of the oronasal membrane begins late in the 11th day (stage 19) with the formation of interstitial gaps. The gaps enlarge and coalesce so that a completely patent opening between nasal passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
(6 reference statements)
1
18
0
Order By: Relevance
“…3A, D). Choanae are bilateral involutions that will form the nasal cavity and provide landmarks for the junction between the primary and secondary palate (Tamarin, 1982). At E11.5, the mesenchymal expression of Barx1 extends nearly along the entire length of the palatal shelf and abuts the posterior limit of the primary choanae (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A, D). Choanae are bilateral involutions that will form the nasal cavity and provide landmarks for the junction between the primary and secondary palate (Tamarin, 1982). At E11.5, the mesenchymal expression of Barx1 extends nearly along the entire length of the palatal shelf and abuts the posterior limit of the primary choanae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3C and F). During the initial stages of secondary palate development, the site of R1 formation is closely associated with the formation of the primary choanae that presages the site of fusion between the primary palate with the anterior secondary palate (Tamarin, 1982). Therefore, growth of the anterior hard palate occurs via the expansion of the domain intervening the FEZ and R1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the forcing of palatal shelves upward by the tongue is not a necessary prerequisite for shelf elevation and that shelf elevation is an active process which can be attained even in the absence of the tongue (Brinkley et al 1974;Walker and Patterson 1974;Wee et al 1976;Zimmerman et al 1983;Shiota et al 1990b); therefore, our culture condition where the lower jaw and tongue are removed does not underestimate the role of the tongue in palatal elevation. Although the primary palate and the nasal septum were suggested to participate in palatal closure (Tamarin 1982), their contribution seems to be limited at least in the initial steps of secondary palate fusion in vitro (Shiota et al 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the topographical development of the primary choanae in the mouse [Pourtois. 1972;Tamarin. 1982;Sim.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of growth of the primary choanae has received little attention. The topographical development of the primary choanae has been described in the mouse [Tamarin, 1982: Sim. 1985].…”
Section: Introductionmentioning
confidence: 99%